Highly Facet‐Dependent Photocatalytic Properties of Cu2O Crystals Established through the Formation of Au‐Decorated Cu2O Heterostructures. Issue 35 (29th July 2016) - Yuan, Guo‐Zhi; Hsia, Chi‐Fu; Lin, Zhen‐Wen; Chiang, Chieh; Chiang, Yun‐Wei; Huang, Michael H.
Abstract: This work confirms the presence of a large facet‐dependent photocatalytic activity of Cu2 O crystals through sparse deposition of gold particles on Cu2 O cubes, octahedra, and rhombic dodecahedra. Au‐decorated Cu2 O rhombic dodecahedra and octahedra showed greatly enhanced photodegradation rates of methyl orange resulting from a better separation of the photogenerated electrons and holes, with the rhombic dodecahedra giving the best efficiency. Au–Cu2 O core–shell rhombic dodecahedra also displayed a better photocatalytic activity than pristine rhombic dodecahedra. However, Au‐deposited Cu2 O cubes, pristine cubes, and Au‐deposited small nanocubes bound by entirely {100} facets are all photocatalytically inactive. X‐ray photoelectron spectra (XPS) showed identical copper peak positions for these Au‐decorated crystals. Remarkably, electron paramagnetic resonance (EPR) measurements indicated a higher production of hydroxyl radicals for the photoirradiated Cu2 O rhombic dodecahedra than for the octahedra, but no radicals were produced from photoirradiated Cu2 O cubes. The Cu2 O {100} face may present a high energy barrier through its large band edge bending and/or electrostatic repulsion, preventing charge carriers from reaching to this surface. The conventional photocatalysis model fails in this case. The facet‐dependent photocatalytic differences should be observable in other semiconductor systems whenever a photoinduced charge‐transfer process occurs across an interface. Abstract : Structure is the key : Whereas Au‐decorated Cu2 O octahedra and rhombic dodecahedra (RD) show enhanced photocatalytic activities compared to their pristine particles, small and large Au‐decorated Cu2 O cubes remain inactive. EPR measurements indicate a higher production of hydroxyl radicals for Cu2 O rhombic dodecahedra than for octahedra upon photoirradiation, but no radicals are produced from photoirradiated Cu2 O cubes (see figure).